Business history around the world - Amatori, Franco; Jones, Geoffrey (Cambridge University Press, 2003)
This book offers the first in-depth international survey of current research and debates in business history. Historians here document and analyze the evolution of a wide range of important companies, their patterns of innovation, production, and distribution, their financial affairs, their political activities, and their social impact.
Keywords: Economic history -- 1990-; Business -- History.; Industrial organization -- Cross-cultural studies.; Histoire économique -- 1990-; Affaires -- Histoire.; Industrie -- Organisation, contrôle, etc. -- Études transculturelles.; BUSINESS & ECONOMICS -- Industries -- General.; Business; Economic history; Industrial organization; Wirtschaft; Kulturvergleich; Since 1990; Electronic books.; Cross-cultural studies; History